SYNTACTIC AND SEMANTIC ANALYSIS ON NADIA MURAD’S NOBEL LECTURE - Autumn Windy Alwasilah; Sutiono Mahdi (Linguistik : Jurnal Bahasa dan Sastra, 2020)
Nadia Murad is known by the world for her dark past. She was one of the victims of sexual harassment by ISIS. She lost his family, she was detained as a slave, burned with cigarettes, and raped. She managed to escape after that he lived with a family, who was able to smuggle her out of territory controlled by the Islamic State, allowing her to go to a refugee camp in Duhok, northern Iraq. On December 16, 2015, she spoke to the United Nation Security Council about human trafficking and conflict. The 2018 Nobel Peace Prize was given to Denis Mukwege and her for their efforts to end the use of sexual violence as a weapon of war and armed conflict. Until now, she is known as a human rights activist.The study focuses on the analysis of adjective phrases in syntax and its meaning in semantic in Nadia Murad’s Nobel lecture. A descriptive qualitative analysis is used to obtain the data. The objectives of this study are to find out the five grammatical functions of adjective phrase proposed by Dixson in Ompungsunggu (2016), and their semantics meaning based on a theory by Downing (2015). It is found that only two grammatical functions of adjective phrase in the lecture, they function as noun phrase modifier and subject complement. While from the semantics meaning, the lecture has a preference to use evaluation descriptor adjective and restrictive classifier adjective.